Variação espacial e temporal dos parâmetros morfológicos em mudas de pinus e eucalipto - Reis, Eduardo Righi dos (2006)
Even whith the advanced of production of seedlings, many problems still exist and they must be solved, mainly in what refers to the expedition of seedlings of the vegetation house. So, this study has as aim to establishes periods and ways of expedition of seedlings of Pinus elliottii Engelm and Eucalyptus grandis W. Hill ex Maid, with uniformity of their morphologic parameters (diameter and height) and to verify the tendency of concentration of the production in reason of their time evaluations, at the forest nursery of Santa Maria Federal University, RS. For that, an experiment was installed in which ten evaluations in intervals of 15 days for Pinus and four evaluations with the same interval of time for Eucalyptus took place, each repetition for each species was divided in portions to determined the best exit form of the seedlings of the vegetation house. The choice of the period of retreat of the seedlings of the vegetation house was based on the result of the analysis of homogeneity of the variances of the morphologic parameters, according to Bartlett's test to 5% of error, and the form of retreat of the seedlings was made comparing the averages through the test t, to 5% of error. It was verified for Pinus, that to the 135 days after the germination, there was already uniformity among its morphologic parameters for the simulations of retreat of seedlings becoming separated the tray in Border x Center (BxC), Right x Center X Left (DxCxE), and Quadrants, and that, to the 180 days, there was uniformity to Front x Center x Bottom (F1xCxF). For Eucalyptus the minimum time of permanence of the seedlings in the vegetation house was of 100 days becoming separated the tray in BxC, F1xCxF and quadrants and of 115 days for them simulation DxCxE. The obtained results, starting from the time of it stayed of the seedlings in the nursery, they allow to conclude that differences exist with relationship to the quality pattern wanted when the seedlings are collected of different places submitted to a same development condition, and that the retreat of the way seedlings assigned that allows to obtain seedlings with the same quality pattern.